Pengaruh Sistem Pengendalian Internal, Kompetensi Aparatur Pengelola Dana Desa, dan Sistem Keuangan Desa Terhadap Akuntabilitas Pengelolaan Dana Desa Se-Kecamatan Petang - putu ari sutrepti; Ni Komang Sumadi; Ni Ketut Muliati (UNHI Press, 2022)
The goals of this study is to determine the effecst of the Internal Control System, Competence of the Village Fund Management Apparatus and the Village Financial System on the Accountability of Village Fund Management throughout the District off Petang. This study use primary data in the form of questionnaire answers. The samples studied in this study were 56 respondents from 7 Village Offices. Determination of the sample using purposive sampling method. Analysis technique that used in this case is multiple linear regression. Based on the result of the analysis, it can be concluded that village financial system has an effect on accountability of village fund management while the internal control system and competence of the village fund management apparatus have no effect on village and management accountability